1969
DOI: 10.1042/bj1130363
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of pepsin-catalysed reactions by products and product analogues. Kinetic evidence for ordered release of products

Abstract: 1. The inhibition of pepsin-catalysed hydrolysis of N-acetyl-l-phenylalanyl-l-phenylalanylglycine by products and product analogues was studied. 2. The non-competitive nature of the inhibition by the product N-acetyl-l-phenylalanine confirms an ordered release of products, and points to a common mechanism (involving an amino-enzyme) for pepsin-catalysed transpeptidation and hydrolysis reactions. 3. N-Acetyl-l-phenylalanine ethyl ester is also a non-competitive inhibitor, but here the inhibition is of the ;dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The patterns of inhibition arising from the presence of acyl product and of chemical and stereochemical analogues of acyl product are reported. The results support and complement the preliminary studies of Greenwell et al (1969), and, together with work reported by Inouye & Fruton (1968) on the inhibition of pepsincatalysed reactions by the second type of product, support the pathway represented by eqn. (1) as operating for pepsin-catalysed hydrolysis, as well as for transpeptidation.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The patterns of inhibition arising from the presence of acyl product and of chemical and stereochemical analogues of acyl product are reported. The results support and complement the preliminary studies of Greenwell et al (1969), and, together with work reported by Inouye & Fruton (1968) on the inhibition of pepsincatalysed reactions by the second type of product, support the pathway represented by eqn. (1) as operating for pepsin-catalysed hydrolysis, as well as for transpeptidation.…”
supporting
confidence: 90%
“…Both these studies were done at pH 2 and relate to inhibition by protonated N-acyl-amino acid. Greenwell et al (1969) have reported a value of 29mM for the inhibition of N-acetyl-L-phenylalanyl-L-phenylalanylglycine by the acyl product N-acetyl-L-phenylalanine at pH 2. The inhibition appeared to be non-competitive, 1971 244 though only a single inhibitor concentration was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-Acetyl-L-[3H]phenylalanine. This compound was prepared from L-[3H]phenylalanine in the way described (for the unlabelled material) by Greenwell, Knowles & Sharp (1969); it had m.p. 169-171°C and [a]20 +46.10 (c 2 in ethanol).…”
Section: Z-mentioning
confidence: 99%